PENGARUH LEVERAGE, GROWTH, PROFITABILITAS, DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Merianti, Desi; Iskak, Jamaludin (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to examine the effect of leverage, growth, profitability, and liquidity on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2020 period. The sample selection technique used is purposive sampling tehcnique with a sample of 43 companies. Data processing in this study using EViews version 12 software. The result of this study indicate that leverage proxied by DER and liquidity proxied by CR has a positive and insignificant effect on dividend policy, profitability proxied by ROE has a negative and insignificant effect on dividend policy, while growth has a negative and significant effect on dividend policy.